2021
DOI: 10.1088/1755-1315/626/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of surrounding rock pressure of large section underground excavation metro station based on the construction process

Abstract: The traditional calculation method of the surrounding strata pressure of the tunnel does not consider the tunnel construction process. The excavation of the large-section tunnel mostly adopts the section excavation method, which is to excavate and support at the same time. The stress state of the pressure of surrounding strata changes gradually during the excavation process. The traditional calculation results of tunnel surrounding strata pressure are generally large. In this paper, the large-section tunnel is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Wang studied the method used for calculating the small clearances of tunnels with large cross-sections. Based on the calculation result of the surrounding rock pressure obtained by the code method, the pressure of the surrounding rock is amplified, or the elastic resistance of the middle sandwich wall is reduced according to the influence law of the smalldiameter distance [15][16][17][18]. As the method used for calculating the surrounding rock loses pressure in a shallow tunnel, a new calculation model used for the surrounding rock pressure in the folded zone is proposed [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang studied the method used for calculating the small clearances of tunnels with large cross-sections. Based on the calculation result of the surrounding rock pressure obtained by the code method, the pressure of the surrounding rock is amplified, or the elastic resistance of the middle sandwich wall is reduced according to the influence law of the smalldiameter distance [15][16][17][18]. As the method used for calculating the surrounding rock loses pressure in a shallow tunnel, a new calculation model used for the surrounding rock pressure in the folded zone is proposed [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sarfarazi et. al., Zhang et al, and Zhang and Qui reported that with the multifactor surrounding rock pressure calculation theory, the surrounding rock pressure of arbitrary shape and span can be easily calculated and analyzed, as well as its stability and safety [20][21][22]. Wen et al [23] introduced the weight coefficients of tunnel depth H, tunnel span B, internal friction angle φ, and rock weight γ and deduced the calculation formula of the surrounding rock pressure for extensive excava-tion of section tunnels.…”
Section: Introductionmentioning
confidence: 99%